Analysis of Security Examination Facilities in Supporting Aviation Safety at Tunggul Wulung Cilacap Airport - Muhammad Rizky Wahyu Nugroho; Fryda Fatmayati (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Various kinds of phenomena that occur at the Tunggul Wulung Cilacap Airport which are managed by the Directorate General of Civil Aviation related to the equipment in the AVSEC unit often experience problems. One of the employees at the unit said that not all of the equipment at the airport was in good condition. This will hinder the passenger inspection process, and can threaten flight safety at the airport itself, therefore this study aims to determine the condition of the equipment in the AVSEC unit, determine the impact caused by the condition of the security inspection equipment that works well on safety. flights and knowing the role of AVSEC officers in overcoming the limitations of flight security inspection equipment at Tunggul Wulung Cilacap Airport. The method used in this study is based on post-positivism philosophy with data collection techniques using triangulation and data analysis is qualitative induction. The research tool is in the form of interviews with each of the senior, junior and basic officers in the Avuation Security (AVSEC) unit. The results of this study can be shown by the results of the researchers' observations that the duties and roles of AVSEC personnel are very good and according to the applicable SOPs, however, the existing inspection facilities will be handled inadequately.